Polysecure : attachment, trauma and consensual nonmonogamy - Fern, Jessica (Thorntree Press, 2020)
"Attachment theory has entered the mainstream, but most discussions focus on how we can cultivate secure monogamous relationships. What if, like many people, you're striving for secure, happy attachments with more than one partner? Polyamorous psychotherapist Jessica Fern breaks new ground by extending attachment theory into the realm of consensual nonmonogamy. Using her Nested Model of attachment and trauma, she expands our understanding of how these emotional experiences influence our relationships. Then, she sets out six specific strategies to help you move toward secure attachments in your multiple relationships. Polysecure is both a trailblazing theoretical treatise and a practical guide. It provides nonmonogamous people with a new set of tools to navigate the complexities of multiple loving relationships, and offers radical new concepts that are sure to influence the conversation about attachment theory"--